Pengaruh Citra Merek dan Kepercayaan merek terhadap Loyalitas Produk Roma Sari Gandum di Wilayah Gresik - Cindy Pramilenia Dewi; Rizky Dermawan (Universitas Batanghari Jambi, 2022)
Brand loyalty is a behavior of consumer loyalty to the brand by repurchasing the same product more than once. The purpose of this research is to find out the effect of brand image and brand trust on brand loyalty.This research uses quantitative methods. The questionnaire survey uses a Likert scale with a population and a sample of 90 consumers in the Gresik area. The selection of this research sample is based on purposive sampling. The results of the analysis using the Partial Least Square (PLS) application with validity tests, reliability tests, and hypothesis testing. The results of the study indicate that the brand image has made a high contribution to brand loyalty in Roma Sari wheat products. Brand trust can contribute to brand loyalty in Roma Sari Gandum Products. It means that the better the brand image produced by a product, the higher the brand loyalty. Even if brand trust, the higher the brand trust, the higher the brand loyalty.